Sachet water in Ghana: A spatiotemporal analysis of the recent upward trend in consumption and its relationship with changing household characteristics, 2010-2017. - Simon Moulds; Anson C H Chan; Jacob D Tetteh; Honor Bixby; George Owusu; Samuel Agyei-Mensah; Majid Ezzati; Wouter Buytaert; Michael R Templeton (PLoS ONE)
The consumption of packaged water in Ghana has grown significantly in recent years. By 2017, "sachet water"-machine-sealed 500ml plastic bags of drinking water-was consumed by 33% of Ghanaian households. Reliance on sachet water has previously been associated with the urban poor, yet recent evidence suggests a customer base which crosses socioeconomic lines. Here, we conduct a repeated cross-sectional analysis of three nationally representative datasets to examine the changing demography of sachet water consumers between 2010 and 2017. Our results show that over the course of the study period sachet water has become a ubiquitous source of drinking water in Ghana, with relatively wealthy households notably increasing their consumption. In 2017, the majority of sachet water drinking households had access to another improved water source. The current rate and form of urbanisation, inadequate water governance, and an emphasis on cost recovery pose significant challenges for the expansion of the piped water supply network, leading us to conclude that sachet water will likely continue to be a prominent source of drinking water in Ghana for the foreseeable future. The main challenge for policymakers is to ensure that the growing sachet water market enhances rather than undermines Ghana's efforts towards achieving universal and equitable access to clean drinking water and sanitation.